2022
DOI: 10.3390/su142315615
|View full text |Cite
|
Sign up to set email alerts
|

Skills Demand in Energy Intensive Industries Targeting Industrial Symbiosis and Energy Efficiency

Abstract: Technological development, closely related to the implementation of industrial symbiosis and energy efficiency, affects all areas of energy intensive industries, and involves the whole industrial workforce. This paper deals with a part of the work developed in the early stage of a current Erasmus+ project, which aims at developing an industry-driven and proactive skills strategy to assist the implementation and exploitation of industrial symbiosis and energy efficiency across the energy intensive sectors. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…The study revealed that the overall implementation of social sustainability indicators was at a high level. Reducing job challenges through employee learning and development programs is a wise approach [50]. The value of human capital in developing employees, highlighting the importance of CSR, and figuring out the best approach to implement it makes it a success factor for firms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The study revealed that the overall implementation of social sustainability indicators was at a high level. Reducing job challenges through employee learning and development programs is a wise approach [50]. The value of human capital in developing employees, highlighting the importance of CSR, and figuring out the best approach to implement it makes it a success factor for firms.…”
Section: Discussionmentioning
confidence: 99%
“…Programs for employee learning and development are a smart way to reduce work difficulties [50]. A competent workforce will be easier to recruit and maintain the introduction of improved information distribution within the business, increased workforce diversity, equitable employment opportunities for all, job security, comparable remuneration, and the career development of the employees [50,51]. The importance of human capital in training people, highlighting the value of CSR, and determining the best way to apply it makes it a criterion of organizational success.…”
Section: Social Concernsmentioning
confidence: 99%
“…In terms of energy industry symbiosis, Butturi et al (2019) expand from energy symbiosis in industrial parks to urban-industry energy symbiosis, arguing that urban-industry energy symbiosis can be realized through collective energy production and management. Branca et al (2022), in their study of labor skill needs for industrial symbiosis in energy-intensive industries, found that the waste treatment processes generated during industrial symbiosis may increase labor demand. Cao et al (2022) in their study of industrial symbiosis between energy industries such as thermal power and hydropower and the social sector across the country found that symbiosis between the thermal power industry and the social sector in terms of waste being able to be reproduced as cement and other symbiotic methods can save a lot of wasted resources and reduce SO 2 emissions and suggested that more emphasis should be placed on industrial symbiosis in the future development of industry.…”
Section: Literature Reviewmentioning
confidence: 99%